(untitled) (European Journal of Education and Psychology, 2020)
The aim of this study was to analyze the coping strategies of daily stress perceived in a sample of university students and its relationship with other psycho-educational variables of empathy and measures of prosocial tendency. The participants were university students belonging to first years of the Education Sciences and Psychology Faculties to whom the following instruments were applied: an Inventory of Coping Strategies, Cognitive and Affective Empathy Test, a Prosocial Scale and another one to evaluate Prosocial Behaviors/Measurement of prosocial tendency. The results proof the existence of positive correlations between productive problem-centered coping strategies such as problem solving and the empathy, prosocial behavior variables, and prosocial trend measurement. The avoidance strategy was negatively associated with the empathy variable and prosocial behavior. The data obtained are relevant for the design of future training programs for coping with everyday stress in the university setting and for the development of intrapersonal and interpersonal skills such as those related to empathy and the development of prosocial behaviors.